EFFECT OF SERVICE QUALITY AND RELATIONSHIP MARKETING ON CUSTOMER SATISFACTION AND ITS IMPACT ON LOYALTY SERVICE ON WISMA SOEWARNA BRACH OFFICE (KCP) OF BNI OF TANGERANG - Ratna Yuwita, Ela; Arissetyanto Nugroho (Dinasti International Journal of Digital Business Management, 2020)
The purpose of this study is to determine the Effect of Service Quality and Relationship Marketing on Customer Satisfaction and Its Impact on Loyalty by measuring indicators that affect the variable Service Quality and Relationship Marketing on customer satisfaction variables and their implications on customer loyalty variables. This research applies a descriptive research design using survey methods. Sampling uses convinient sampling as a sampling technique. This study was tested using the structural equation modeling (Lisrel) approach to test the significance of the significance of the overall model and predetermined pathway. The findings show that Service Quality and Relationship Marketing variables significantly influence customer satisfaction variables. Further findings indicate that Service Quality and Relationship Marketing variables directly have a significant effect on customer loyalty variables. This study also shows that customer satisfaction has an influence on customer loyalty variables. It is recommended to companies to improve the excellence of Service Quality and Relationship Marketing.